Retinal Disorders and Sleep Disorders: Are They Genetically Related?. (September 2015) - Murphy, Caitlin; Duponsel, Nathalie; Huang, Xi Sheila; Wittich, Walter; Koenekoop, Robert K.; Overbury, Olga
Introduction: Sleep is important for optimal physical health and vitality. Recent studies have shown that individuals with visual impairments may be at risk for sleep problems. This research examines the prevalence of sleep problems among those with retinal disorders and the possibility of a genetic link. Methods: Subjects with retinitis pigmentosa ( n = 33), Stargardt's disease ( n = 31) and age-related macular degeneration ( n = 43) were recruited from the ophthalmology department of Montreal Children's Hospital. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS). Genetic testing was conducted by the Radboud University Medical Center in Nijmegen, Netherlands. Retinal genes were identified as having retina only or pineal and retinal expression. Results: The expression patterns of genes causing retinal disorders did not predict sleep quality. The PSQI indicated poor sleep quality in 56% of participants with retinitis pigmentosa, 48% of those with Stargardt's disease, and 53% of those with age-related macular degeneration. The ESS showed that daytime sleepiness was experienced by 20% of individuals with retinitis pigmentosa or Stargardt's disease, and by only one individual with age-related macular degeneration. Discussion: Approximately 50% of people with retinal disease have sleep problems. This number compares with up to one-third of the general population. Gene expression did not correlate with sleep quality, and the explanation for such a large percentage of sleep disorders needs further investigation. Implications for practitioners: Eye care and rehabilitation specialists need to be aware of the high prevalence of poor sleep quality in individuals with retinal disorders, since this situation may have an important impact on memory and learning, both of which are vital in successful rehabilitation.